Smart architecture for software-defined networking - Mejia, Jose; Cruz-Mejia, Oliverio; Acosta-Favela, José Alfredo; Mendoza-Carreón, Alejandra; Noriega-Armendáriz, René (Cultura Científica y Tecnológica, 2022)
Software-defined networks (SDN) seek to solve the problems in current network schemes by simplifying their management through their reprogrammability and accessibility to the overall network infrastructure. One aspect to improve in SDN-based schemes is the precise classification of your traffic load, this can improve various aspects such as quality of service, dynamic access control, prioritized random access, among others. This research aims to propose a conceptual architecture of SDN and evaluate different machine learning methods for traffic classification. To this end, SDN architectures are analyzed and different modules are proposed to strengthen their management with the help of low computational cost classifiers. The architecture proposes the following main modules: Capture network traces module, Learning Engine module, and ML-model and Flow classifier. To determine the model to be used in the Learning Engine and Flow classifier modules, different classifiers were evaluated using a database of network traffic, as a result, it was determined that the gradient boosting algorithm is the most suitable to be integrated with the proposed SDN architecture.